Effectiveness Of Early Truncal Facilitation Techniques On Balance And Functional Mobility In Post Stroke Patients. - Diwan, Nayala; G., Varadharajulu; Kanase, Suraj (International Journal of Psychosocial Rehabilitation, 2020)
OBJECTIVES: To find the effectiveness of early truncal facilitation techniques on balance and functional mobility in post-stroke patients. MATERIAL AND METHODOLOGY: An experimental study was conducted at the physiotherapy department of Krishna College of Physiotherapy. A total of 30 patients were allotted to a single group using convenient sampling and consecutive sampling methods. This group was given early truncal facilitation techniques on post-stroke patients. STATISTICAL ANALYSIS—Data was analyzed using a paired ‘t’ test. RESULTS: Statistical analysis was performed using paired t-test Intragroup comparison (within group) was analyzed for TIS for balance and FIMS for functional mobility. The mean TIS score on pre-intervention was 6.06+3.29, which was increased to a mean of 16.53+4.041 post-sessions. The p-value by paired t-test was found to be <0.0001, which is extremely significant. Whereas the mean FIMS score pre-intervention was 49.33+3.20.65, which was increased to a mean of 81.96+21.19 post-intervention. The p-value by paired t-test was found to be <0.0001, which is extremely significant. CONCLUSION: From this study, it can be concluded that there was extremely significant improvement in subjects who underwent early truncal impairment on post-stroke patients statistically and clinically. Hence this study accepts the alternate hypothesis (H1)